PSXVII-38 Metabolic efficiency in swine determined with automated real time infrared thermography. (7th December 2018) - Schaefer, A; von Gaza, H; Cook, N; Bench, C; Charagu, P; Simpson, G; Huisman, A
Abstract: The cost of production for pork is largely dependent on the metabolic efficiency and feed requirements of swine. Furthermore, metabolic efficiency affects the retail cost and availability of high density food as well as the carbon footprint and waste management burden for the swine industry. Conventional methodology for measuring metabolic efficiency, such as determining residual feed intake (RFI), with feed stations is time consuming and expensive. Moreover, determinations are often not available until well into the growth cycle of the animal. Recent technology developments using infrared thermography have demonstrated that metabolic efficiency can be determined within 24h and on pigs at a young age using a non-invasive, automated infrared procedure. Studies were undertaken on both research herds and commercial herds to examine the relationship between an infrared thermal profile and metabolic efficiency. The research herd consisted of 132 crossbred barrows and gilts (Duroc X Landrace-York) (Alberta Agriculture, Lacombe Alberta). The commercial herd consisted of 1315 Duroc boars and gilts managed by Hypor Comp. Regina Saskatchewan. The studies demonstrated a statistically significant relationship between conventional RFI values and Feed Conversion Efficiency or FCE values (Feed/gain determined with Nedap® and Firestart ® feed stations) and an Infrared Thermal Index determined with FLIR automation cameras (r=0.3 to 0.5, P<0.05). In addition, animals displaying aberrant health conditions, notably fevers, were also identified with infrared which were not apparent with feed intake data. The current studies suggest thermal phenotypic measurements demonstrate utility in identifying animals displaying superior metabolic efficiency.